1995
DOI: 10.4012/dmj.14.120
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year Longitudinal Clinical Evaluation of a Visible Light Cured Posterior Composite Resin

Abstract: Using modified USPHS criteria, we evaluated annually for ten years 91 cases restored with visible light cured posterior composite resin LFP (Base resin: UDMA; filler: micro crushed type, alumino-silicate, barium glass and silica, 85wt%, 74vol%). The 91 cases restored with LFP decreased to 68 in ten years. Of the 23 cases that were lost, one resulted from a pulpal reaction immediately following restoration, four were extracted owing to periodontal disease or extrusion of third molars, two became abutments owing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 5 publications
1
27
1
2
Order By: Relevance
“…More than 10-year (10 and 17 years) survival rates of Class I restorations ranged from 69.4 % to 100 % in 3 clinical trials [8,18,19], however, it must be noted that the 100 % was obtained from the very small sample size (n=4). Around 10-years (4.8 -17 years) survival rates of…”
Section: Prospective Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…More than 10-year (10 and 17 years) survival rates of Class I restorations ranged from 69.4 % to 100 % in 3 clinical trials [8,18,19], however, it must be noted that the 100 % was obtained from the very small sample size (n=4). Around 10-years (4.8 -17 years) survival rates of…”
Section: Prospective Studiesmentioning
confidence: 99%
“…Class II restorations ranged from 58.3 % to 100 % in 9 clinical trials [8,10,12,15,[17][18][19][20][21].…”
Section: Prospective Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have since been carried out to investigate the wear of composite resins [1][2][3] , and most of them showed that wear is inevitable. In our recent study 4) on wear of composite resins which contained large organic composite filler particles with nano-sized inorganic particles, they displayed markedly lower wear than other types of composite resins.…”
Section: Introductionmentioning
confidence: 99%
“…However, the wear property of restorative dental materials is very complicated due to a variety of factors. In a study that involved a ten-year clinical evaluation of a posterior composite resin 5) , 37% of the restorations exhibited nonanatomical change whereas 7% deteriorated over the span of 10 years. The remaining 56% were evaluated as slightly deteriorated in some region.…”
Section: Introductionmentioning
confidence: 99%